DETERMINASI SOSIAL LINGKUNGAN KERJA DAN EPIDEMIOLOGI MANAJERIAL: TINJAUAN LITERATUR DAMPAK KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA MELALUI MEDIASI KEPUASAN KERJA PERAWAT DI RSUD PROVINSI NTB - Nursini Juiban Hadi; Yuly Peristiowati (Bajang Institute, 2026)
Background: Nurse performance at RSUD Provinsi NTB is a fundamental pillar of public healthcare quality. However, this performance is influenced by complex factors involving social determinants of the work environment and leadership patterns. Objective: This study aims to analyze the influence of transformational leadership and motivation on nurse performance through the mediation of job satisfaction within a managerial epidemiology perspective. Methods: This study employed a Systematic Literature Review (SLR) method. The literature search was conducted via Scopus and Google Scholar databases covering the period 2014-2024. Article selection followed strict inclusion and exclusion criteria, resulting in 10 relevant real-world articles. Results: Findings indicate that transformational leadership and motivation have a significant positive impact on performance. Job satisfaction was identified as a crucial mediating variable; without adequate job satisfaction, the impetus from leadership and motivation fails to achieve optimal performance outcomes. Managerially, the work environment acts as a primary determinant that must be managed to prevent an